2022
DOI: 10.9734/ajsspn/2022/v8i130131
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Organic and Inorganic Fertilizers on Yield and Yield Contributing Characters of Mustard (Brassica napus L.)

Abstract: Bangladesh is a densely populated country where the oil crisis is one of the major issues. On the other hand, the balanced fertilizer used is lacking until now. The purpose of the study is to investigate the yield of Mustard (Brassica napus L.) Binasarisha-9 is influenced by the different applications of organic fertilizers. The experiment was conducted at Bangladesh Institute of Nuclear Agriculture (BINA), substation, Satkhira during the rabi season of 2020-2021 to observe the effect of organic and inorganic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…A similar result was also observed by Reza et al, (2022) andTripathi et al, (2010) who narrated that application of 50% RDCF along with vermicompost produced the highest yield and yield attributes of mustard. Furthermore, the combined application of 75% RDCF with 3 t ha -1 vermicompost also may reduce the risk of salinity stress on mustard yield.…”
Section: Effects Of Combined Application Of Inorganic and Organic Fer...supporting
confidence: 86%
See 1 more Smart Citation
“…A similar result was also observed by Reza et al, (2022) andTripathi et al, (2010) who narrated that application of 50% RDCF along with vermicompost produced the highest yield and yield attributes of mustard. Furthermore, the combined application of 75% RDCF with 3 t ha -1 vermicompost also may reduce the risk of salinity stress on mustard yield.…”
Section: Effects Of Combined Application Of Inorganic and Organic Fer...supporting
confidence: 86%
“…These findings also revealed that the application of chemical fertilizers along with vermicomposting may mitigate the salinity effects on the mustard plant. A similar result was also observed by Reza et al, (2022) where the application of vermicompost along with chemical fertilizer improved mustard plant growth. In a column figures having similar letter (s) do not differ significantly whereas figures with dissimilar letter (s) differ significantly as per LSD at 5% level of probability.…”
Section: Influence Of Combined Application Of Organic and Inorganic F...supporting
confidence: 84%
“…Additionally, due to the crops' extraction of nutrients from the soil's reserves, a deficiency in nutrients ensued. Reza et al [ 46 ], who utilized both wholly inorganic fertilizer and a blend of organic and inorganic fertilizer, likewise achieved identical outcomes.…”
Section: Resultsmentioning
confidence: 99%